Scaling Drought And Flood-Tolerant Rice Varieties, Good Agricultural Practices, And Pest And Disease Management: Insights And Lessons Learned From 2022 To 2025 - Suh, Neville Ndohnwi; Dolo, Minindou; Dossou Yovo, Elliott Ronald (2025)
Climate change impacts remain a significant risk to rice production in Mali, affecting rice productivity and farmers' livelihoods. Pilot programs of climate-smart agriculture (CSA) innovations have shown that the use of drought- and flood–tolerant rice varieties, combined with good agricultural practices and integrated pest management, is key to increasing rice yields during periods of climate risk. Given the need for sustained scaling of CSA innovations in rice production systems in Mali, a one-day capacity-building workshop was held on the 19th of November in Bamako. With over 8980 farmers having adopted climate-smart rice varieties (about 54% of whom are women) between 2022 and 2025, the workshop aims to continue promoting the widespread adoption of improved seeds. The workshop also aimed to build the capacity of lead farmers, extension agents, service providers, partner NGOs, and government agencies in integrated practices for climate-smart rice varieties, good agricultural practices, and pest and disease management, which are key to increased rice yields and climate resilience. The workshop also identified key constraints to scaling and adoption of bundle CSA practices, highlighting insights and lessons learned from scaling innovations between 2022 and 2025 and identifying areas for improvement.